A Survey on Contemporary Terrestrial and Handheld Multimedia Broadcasting Networks - Charalampos N. Pitas; Athanasios D. Panagopoulos; Philip Constantinou (Communications - Scientific letters of the University of Zilina, 2012)
Digital video broadcasting (DVB) transmission technologies are suitable for wireless delivery of multimedia content both to static and mobile end-users. On the one hand, DVB-T standard has been adopted for digital terrestrial television (DTT) and it has been further developed into a newer standard, DVB-T2, which was recently finalized. On the other hand, DVB-H is a specification for the transmission of digital TV to handheld user terminals such as smart phones delivering IP-encapsulated data. The combination of satellite and terrestrial DVB technologies is DVB-SH which delivers wide coverage to mobile terminals and promises upgraded services to mobile and vehicle users via a satellite link. The objective of our research article is to present a survey on terrestrial, mobile and hybrid DVB multimedia networks. Emphasis will be given on quality of radio and service related aspects. A focus on performance evaluation methodology based mainly on measurement campaign will be proposed with a detailed presentation of experimental equipment for drive-test field measurements. Guidelines of measurements and analysis processes will be described. A public DVB network in the area of Athens will be our case study.